An Electrochemical Study of the Influence of Marinobacter aquaeolei on the Alteration of Hydrothermal Chalcopyrite (CuFeS2) and Pyrite (FeS2) under Circumneutral Conditions - Aazani, Mujahid; Müller, Moritz; Mills, Rachel A.; Pearce, Richard B.; Milton, James A.; Statham, Peter J.; Lloyd, Jonathan R.; Denuault, Guy D. (Taylor & Francis, 2014)
Pyrite and chalcopyrite are the two most abundant sulphides observed in seafloor hydrothermal systems. The alteration of sulphides is primarily controlled by reactions on the mineral surfaces and Fe(II)-oxidizing bacteria closely related to Marinobacter aquaeolei are thought to play a major role in iron oxidation under circumneutral conditions. We assessed the influence of M. aquaeolei on the electroactivity of FeS2 and CuFeS2 minerals under circumneutral conditions. Samples for the experiments were obtained from the Trans-Atlantic Geotraverse (TAG) hydrothermal mound (field), 26 ◦N on the Mid-Atlantic Ridge and Ireland (CuFeS2)]. The experimental approach relied on voltammetry and scanning electrochemical microscopy (SECM). The tip-substrate voltammetry mode of SECM was found to be particularly suitable to probe the major redox processes of those minerals and permitted an assessment of the microorganisms influence on these processes. M. aquaeolei was found to enhance FeS2 and CuFeS2 oxidation, particularly under suboxic conditions. M. aquaeolei also significantly enhances Fe dissolution under oxic circumneutral conditions but suppresses the dissolution of most other elements compared to abiotic conditions. Under abiotic conditions the surfaces of the minerals are rapidly passivated when oxygen is available; while addition of M. aquaeolei significantly hinders the passivation of chalcopyrite, no passivation of the pyrite surface is observed. This study demonstrates the ability of Marinobacter aquaeolei to enhance oxidation of FeS2 and CuFeS2 under circumneutral conditions and supports the involvement of Marinobacter species in weathering reactions on the seafloor and the control of the ultimate fate of sulphide deposits.